2016
DOI: 10.5194/aab-59-9-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sex influence on genetic expressions of early growth in Afshari lambs

Abstract: Abstract. Very little is known about the genetic aspects of sexual dimorphism of body weight in domestic sheep, and therefore this study was conducted to quantify the genetic basis of sexual dimorphism for earlygrowth-related traits in Afshari lambs. Traits evaluated included birth weight (BW), weaning weight (WW), and growth rate (GR) in male and female lambs. Male lambs were 6.6 % heavier at birth, had 14.4 % higher preweaning growth rates and were 16.0 % heavier at weaning compared to female lambs. Levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…Significantly faster growth intensity of single lambs compared to those from multiple litters (Dixit et al, 2001;Ptáček et al, 2013) was demonstrated in our study as well. Similarly better growth ability of males were previously confirmed by Momani Shaker et al (2010), Taskin et al (2012), Simeonov et al (2014) and Ghafouri-Kesbi and Notter (2016). Differences between the sexes may be due to the different configuration and muscle growth of females and male lambs.…”
Section: Growth Analysissupporting
confidence: 68%
“…Significantly faster growth intensity of single lambs compared to those from multiple litters (Dixit et al, 2001;Ptáček et al, 2013) was demonstrated in our study as well. Similarly better growth ability of males were previously confirmed by Momani Shaker et al (2010), Taskin et al (2012), Simeonov et al (2014) and Ghafouri-Kesbi and Notter (2016). Differences between the sexes may be due to the different configuration and muscle growth of females and male lambs.…”
Section: Growth Analysissupporting
confidence: 68%
“…Hence, an obvious superiority of Karakul sheep over the Awassi sheep was found to be associated with several traits measured. However, the involvement of sex and dam-age could not be excluded from this explanation [12]. In contrast with the pre-sexual maturity, an increasing significant association of the GnRH1 genotypes with growth traits was detected in post-sexual maturity.…”
Section: Discussionmentioning
confidence: 90%
“…) , where x ̅ was the mean number of samples (x) and σ A 2 was additive genetic variance (Ghafouri-Kesbi et al, 2016).…”
Section: Bayesian Estimation and Priorsmentioning
confidence: 99%